2013
DOI: 10.1007/s00425-012-1827-3
|View full text |Cite
|
Sign up to set email alerts
|

HVP10 encoding V-PPase is a prime candidate for the barley HvNax3 sodium exclusion gene: evidence from fine mapping and expression analysis

Abstract: In cereals, a common salinity tolerance mechanism is to limit accumulation of Na(+) in the shoot. In a cross between the barley variety Barque-73 (Hordeum vulgare ssp. vulgare) and the accession CPI-71284 of wild barley (H. vulgare ssp. spontaneum), the HvNax3 locus on chromosome 7H was found to determine a ~10-25 % difference in leaf Na(+) accumulation in seedlings grown in saline hydroponics, with the beneficial exclusion trait originating from the wild parent. The Na(+) exclusion allele was also associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 61 publications
0
35
0
Order By: Relevance
“…Frozen leaf samples were ground as described above for DNA extraction. TRIsol-like reagent was used for RNA extraction following the protocol published earlier (Shavrukov et al, 2013) and the quality of RNA was checked on agarose gels. After treatment with 1 μl of DNase (Quigen, Germany), the MoMLV Reverse Transcriptase kit (Biosan, Novosibirsk, Russia) was used to construct first-strand cDNA reactions which included 2 μg of each RNA sample, oligo(dT) 20 primer and dNTPs as recommended by the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
“…Frozen leaf samples were ground as described above for DNA extraction. TRIsol-like reagent was used for RNA extraction following the protocol published earlier (Shavrukov et al, 2013) and the quality of RNA was checked on agarose gels. After treatment with 1 μl of DNase (Quigen, Germany), the MoMLV Reverse Transcriptase kit (Biosan, Novosibirsk, Russia) was used to construct first-strand cDNA reactions which included 2 μg of each RNA sample, oligo(dT) 20 primer and dNTPs as recommended by the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
“…It should also be noted that only one time point was used for the expression studies, and expression of genes encoding salt tolerance gene has been shown to fluctuate between days (e.g. HVP10 in [63]). Lastly, it should also be noted the NHX1 and NHX2 genes in barley are homologues of AtNHX1 and, while having similar nucleotide sequence may not necessarily confer the protein(s) function as AtNHX1 in Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…HVP10 was proposed as a strong candidate underlying HvNax3, a locus on the short arm of chromosome 7H identified in a bi-parental population resulting from a cross between the wild barley CPI-71284-48 (Hordeum vulgare ssp. spontaneum) and the cultivar Barque-73 (Shavrukov et al 2013;Shavrukov et al 2010). HvNax3 was found to be associated with Na + exclusion, explaining 10-25% difference in leaf Na + of plants grown hydroponically under salinity (Shavrukov et al 2013).…”
Section: Soil Salinitymentioning
confidence: 92%